2019
DOI: 10.1111/jfpp.14266
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic, flavonoid, and amino acid compositions reveal that selected tropical seaweeds have the potential to be functional food ingredients

Abstract: Seaweeds are a rich source of metabolites, including polyphenols, flavonoid, and amino acids, and have been used as food or food supplements in Asian countries since ancient times. Different metabolites are being reported from seaweeds worldwide, but there has been little reported, so far, on tropical seaweeds of the Arabian Sea coast. Eighteen abundant tropical seaweeds (7 green, 4 brown, and 7 red) were collected from the Saurashtra Coast of the Arabian Sea (Gujarat, India), and their phenolic, flavonoid, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 49 publications
3
44
1
Order By: Relevance
“…Among the natural antioxidants, widely distributed plant flavonoids and phenolic constituents merit emphasis because of their involvement in cellular plant defence systems and are therefore considered as potent antioxidants [13,33,57]. Psyllium plant parts contained higher contents of total flavonoids and total phenols and possessed high antioxidant and scavenging activities [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the natural antioxidants, widely distributed plant flavonoids and phenolic constituents merit emphasis because of their involvement in cellular plant defence systems and are therefore considered as potent antioxidants [13,33,57]. Psyllium plant parts contained higher contents of total flavonoids and total phenols and possessed high antioxidant and scavenging activities [45].…”
Section: Discussionmentioning
confidence: 99%
“…The reaction mixture was diluted with water and absorbance was recorded at 510 nm. The total flavonoid content was calculated as mg ml − 1 quercetin per 100 mg of extract from a standard curve [57,66].…”
Section: Determination Of Total Phenolic and Total Flavonoid Contentsmentioning
confidence: 99%
“…A recent study has described the presence of myricetin, among other flavonoids, in Caulerpa spp. [53]. The last study revealed that Caulerpa spp.…”
Section: Discussionmentioning
confidence: 99%
“…Brown seaweeds present higher contents of benzoic and cinnamic acids (1 mg/g) than red (0.2 3 mg/g) and green (0.01–0.9 mg/g) seaweeds [ 26 , 104 , 105 ]. Higher values (1–9 mg/g) have been reported for gallic acid in green and red seaweeds [ 106 ]. These authors reported catechin content up to 14 mg/g in red seaweeds and up to 11.5 mg/g in green ones, whereas in brown seaweeds reached up to 11 mg/g.…”
Section: Marine Phenolics: Sources and Phenolic Compositionmentioning
confidence: 99%